Effects of home disease management strategies based on the dyadic illness management theory on elderly patients with chronic heart failure and informal caregivers’ physical and psychological outcomes: a randomized controlled trial - Zhou, Taihua; Hu, Yaoyao; Zhu, Lingyun; Zhu, Ping; Ji, Xingxing; Wang, Jia; Shang, Hui; Zhao, Chence (Frontiers in Medicine, 2025)
ObjectiveThe purpose of our study was to consider elderly patients with chronic heart failure (CHF) and informal caregivers as a unit of intervention and to explore the effectiveness of a program developed based on dyadic illness management theory in improving their physical and psychological health.MethodsIn this single-center randomized controlled trial, 80 dyads of elderly CHF patients and their informal caregivers were randomly assigned (1:1) to an intervention group receiving a 3-month home-based disease management program or a control group receiving usual care. Data on primary outcome (patient QoL) and secondary outcomes (e.g., patient self-management, readmission, depression, and caregiver burden) were collected at baseline (T0), immediately post-intervention (T1), and 3 months post-intervention (T2).ResultsAt both T1 and T2, patients in the intervention group showed significantly better outcomes than controls in QoL, readmission rates, self-care behaviors, and depression incidence (all p < 0.05). Caregiver burden was consistently lower in the intervention group at both timepoints (all p < 0.05). QoL showed temporal improvements in the intervention group, with sustained enhancement at both T1 and T2 (compared to baseline) and further progression from T1 to T2. In contrast, the control group demonstrated only transient improvement at T1 (compared to baseline), followed by decline at T2. After adjusting for baseline factors, the intervention demonstrated a significant and independent effect on improving patient QoL. This effect was not only sustained but substantially strengthened from T1 (B = −6.855) to T2 (B = -25.00, both p < 0.001), indicating a cumulative benefit over time. The model for T2 accounted for the majority of the outcome variance (adjusted R2 = 0.828).ConclusionThe home-based, dyadically-focused disease management program significantly improved both physical and psychological health outcomes for elderly CHF patients and their caregivers. And substantially increasing improvements in patients’ QoL.